PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN REPRESENTASI MATEMATIS PESERTA DIDIK KELAS VII.1 SMPN 12 PEKANBARU - Hanum, Rodliah; Roza, Yenita; Kartini, Kartini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims improve the learning process and the student’s mathematical representation skill by applying Problem Based Learning (PBL) model. The subject were 36 students of class VII.1 SMPN 12 Pekanbaru. This study was conducted in the fisrt semester of academic year 2018/2019. This research is Classroom Action Research with two cycles and each of cycle has four stages: planning, implementation, observation, dan reflection. Data used in this research are qualitative and quantitative data. The research instruments used are mathematical learning instruments (Syllabus, Lesson Plans, and Student Activity Sheets). Instruments for data collecting (Observation Sheets and Mathematical-Representation Tests). Techniques of data collection are observation and test. Data analysis techniques are descriptive narrative analysis and descriptive statistics analysis. The result showed that implementation of learning process on cycle II had improved from implementation on cycle I. The result of this study showed that the implementation of Problem Based Learning improved student’s Mathematical Representation skill. The mean of the student’s learning achievement for the first cycle is 40.53 (low) which is 63.89 (moderate) had improved to 82.87 (high) in cycle II. This study concludes that the implementation of Prolem Based Learning model improved the learning process and improve the student’s mathematical representation skill at class VII.1 SMPN 12 Pekanbaru.Key Words: Problem based learning, mathematical representation skill, learning process